A descriptive Qualitative Study on Understanding the Factors Influencing Acceptance of Wearable Device Integration in Prenatal Care - Ahonen, Peninah (My University, 2024)
Prenatal care is important in ensuring the optimal health and well-being of pregnant women. Recently, there has been growing interest in integrating wearable devices into prenatal care to enhance monitoring and management during pregnancy. However, the factors influencing pregnant women’s decisions to accept or reject these devises remain underexplored. This thesis uses the Unified Theory of Acceptance and Use of Technology (UTAUT) as its framework to investigate these factors through a descriptive qualitative study. The research aims to explore the acceptability of wearable smart ring technology within a prenatal care setting. The study involved twenty pregnant women (n=20) selected via convenience sampling from maternity clinics in Turku, Finland. Findings revealed that perceived usefulness, effort expectancy, social influence, and facilitating conditions shaped attitudes towards wearable technology and were important for acceptance and adoption. This study offers insights into integrating wearable technology into prenatal care, highlighting both barriers and facilitators of wearable technology during pregnancy.

摘要 目的 探讨孕妇接受可穿戴智能戒指的障碍因素和促进因素。 方法 采用描述性质性研究。使用 2020 年对某地妇科门诊 20 名孕妇进行的结构化访谈数据，通过主题分析法进行内容分析。孕妇的纳入标准为孕周≥13 周，年龄≥18 岁，能够使用智能手机，能够熟练使用英语和芬兰语。 结果 孕妇感知可穿戴技术的有用性取决它的具体功能，包括睡眠监测、体力活动监测以及与医疗环境的融合等。孕妇对可穿戴技术的期望还受到技术参与、技术挑战以及是否能够融入日常生活的影响。此外，社会影响，特别是医疗提供者的建议也在塑造孕妇对可穿戴技术的态度方面发挥了重要作用。个性化、定制以及功能性等促进条件对于提高孕妇的接受和采纳程度同样至关重要。 结论 将可穿戴技术有效地整合到产前护理中，并充分了解孕妇在孕期使用可穿戴技术的障碍和促进因素，有助于更好地理解孕妇对可穿戴技术的接受度，并为未来的研究和实际应用提供了有价值经验。 关键词：孕妇、怀孕、接受、Oura戒指、可穿戴技术、智能戒指、统一的接受和技术使用理论
Keywords: pregnant women, pregnancy, acceptance, Oura ring, wearable technology, smart ring, unified theory of acceptance and use of technology.